Topological single-photon emission from quantum emitter chains - Wang, Yubin (2024)
We propose a scheme for generating highly indistinguishable single photons from an active quantum Su-Schrieffer-Heeger chain composed of a collection of noisy quantum emitters. Strikingly, the single photon emission spectrum of the active quantum chain is exceedingly narrow relative to that of a single emitter or a topologically trivial chain. Furthermore, this effect is amplified dramatically in proximity to the non-trivial-to-trivial phase transition point. Exploiting this effect, we demonstrate that the single-photon linewidth of a long topological quantum chain can be arbitrarily reduced, rendering it an ideal source of indistinguishable single photons. Finally, by analyzing the most critical parameters concerning experimental realization and providing a microscopic and quantitative analysis of our model, we take concrete examples of actual quantum emitters to establish the viability of our proposal.